The infinite sea / 2. - Yancey, Richard (5th wave, 2014)
"Cassie Sullivan and her companions lived through the Others' four waves of destruction. Now, with the human race nearly exterminated and the 5th Wave rolling across the landscape, they face a choice: brace for winter and hope for Evan Walker's return, or set out in search of other survivors before the enemy closes in"--Provided by publisher.